Acurácia do teste cutâneo de leitura tardia na alergia à proteína do leite de vaca com manifestações gastrointestinais - Gonzaga, Thamiris Almeida (2016)
Food allergy is an adverse reaction to food that occurs after ingestion with involvement of immunological mechanisms. The clinical manifestations of non-IgE-mediated type are characterized by the late appearance of symptoms. Objective: to evaluate the accuracy of the late-reading skin test, also known as atopy patch test for predicting oral tolerance after treatment with exclusion diet in patients with the diagnosis of non-IgE-mediated cow's milk protein allergy and gastrointestinal symptoms. Methods: A cross-sectional study with the participation of 32 patients diagnosed with non-IgE-mediated cow's milk protein allergy with gastrointestinal manifestations. After at least of 90 days on diet exclusion, the patients performed atopy patch test with 3 different cow’s milk protein preparations (in natura 2% in saline solution and 2% in petrolatum) and the oral food challenge. Results: Six (18.7%) patients presented positive oral food challenge. No differences in gender, onset symptoms age, oral food challenge age, Z-score, and exclusion period were found between positive and negative oral food challenge patients. Preparations in natura and with petrolatum presented sensitivity equal to zero and specificity 92.3% and 96.1%. The preparation in saline solution showed sensitivity and specificity of 33.3% and 96.1%. Conclusion: The results showed a low accuracy of atopy patch test for cow's milk protein in this group of patients and, therefore, remain not recommended for clinical use.